2002
DOI: 10.2514/2.3880
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Analysis of a Lifting Body Launch Vehicle

Abstract: As part of phase 2 of the X-33 Program, NASA selected an integrated lifting body/aerospike engine con guration as the study vehicle for the conceptual analysis of a single-stage-to-orbit reusable launch vehicle. A team at NASA Langley Research Center participated in the screening and evaluation of a number of proposed vehicle con gurations in the early phases of the conceptual design process. The performance analyses that supported these studies were conducted to assess the effect of the vehicle's lifting capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The trajectory for this vehicle had been carefully tailored to delay the onset of transition. 6 The main concern is for premature boundary layer transition during the extreme heating portions of the flight (up to 1500 s), where boundary layer transition could results in significant augmentation of the already high heating rates, resulting in TPS exceeding its temperature limits, and having a significantly higher integrated heat load. The resulting temperature differences across the honeycomb panel thickness at the three axial stations of 6.1, 20.4 and 30.4 m are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trajectory for this vehicle had been carefully tailored to delay the onset of transition. 6 The main concern is for premature boundary layer transition during the extreme heating portions of the flight (up to 1500 s), where boundary layer transition could results in significant augmentation of the already high heating rates, resulting in TPS exceeding its temperature limits, and having a significantly higher integrated heat load. The resulting temperature differences across the honeycomb panel thickness at the three axial stations of 6.1, 20.4 and 30.4 m are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 where the vehicle reentry altitude, velocity, and Mach number histories are shown. 6 This is a 2570 s long reentry, with reentry velocity of 7.63 km/s at an altitude of 122 km. The flow is hypersonic until 1970 s into reentry.…”
Section: Vehicle and Tpsmentioning
confidence: 99%
“…Single-stage-to-orbit (SSTO) launch systems, such as the X-33 (see Ref. 3), have been studied because this configuration is ideal for reuse similar to that of aircraft. However, these studies indicated that the SSTO configuration had difficulties because it would require a higher performance propulsion system and greater reduction of its structure weight than can be attained based on the present technology.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in automation of multi-disciplinary design and analysis process has been getting faster in recent years using various analysis tools. [1][2][3][4][5][6][7][8] The two main challenges of Multi-Disciplinary Design Optimization (MDO) are computational expense and organizational complexity. In this regard, mathematical modeling and formulation of the design problem play the main role.…”
Section: Introductionmentioning
confidence: 99%